2006
DOI: 10.1242/jeb.02325
|View full text |Cite
|
Sign up to set email alerts
|

Material properties and biochemical composition of mineralized vertebral cartilage in seven elasmobranch species (Chondrichthyes)

Abstract: SUMMARY Elasmobranchs, particularly sharks, function at speed and size extremes,exerting large forces on their cartilaginous skeletons while swimming. This casts doubt on the generalization that cartilaginous skeletons are mechanically inferior to bony skeletons, a proposition that has never been experimentally verified. We tested mineralized vertebral centra from seven species of elasmobranch fishes: six sharks and one axially undulating electric ray. Species were chosen to represent a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 50 publications
7
100
1
Order By: Relevance
“…However, the only previously reported value of material stiffness in a batoid skeletal element [vertebrae from a basal electric ray, Torpedo californica (Porter et al, 2006)] is much lower than this study's values for the closely related N. bancroftii (25 and 1300MPa, respectively). This difference may reflect the functional differences between these two skeletal elements: the propterygia continually experience punting forces, whereas vertebrae are hypothesized to experience very low stresses during axial undulation (Porter et al, 2006). Additionally, this may reflect differences in the compressive versus bending loads for which the vertebrae and propterygia were being tested, respectively.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…However, the only previously reported value of material stiffness in a batoid skeletal element [vertebrae from a basal electric ray, Torpedo californica (Porter et al, 2006)] is much lower than this study's values for the closely related N. bancroftii (25 and 1300MPa, respectively). This difference may reflect the functional differences between these two skeletal elements: the propterygia continually experience punting forces, whereas vertebrae are hypothesized to experience very low stresses during axial undulation (Porter et al, 2006). Additionally, this may reflect differences in the compressive versus bending loads for which the vertebrae and propterygia were being tested, respectively.…”
Section: Discussioncontrasting
confidence: 88%
“…Although there are no reported values of skeletal flexural stiffness in other elasmobranchs, material stiffness values for shark vertebrae when under compression [322-978MPa (Porter et al, 2006;Porter et al, 2007)] are within the lower range of values that were found for the appendicular propterygium during bending (140-2533MPa). However, the only previously reported value of material stiffness in a batoid skeletal element [vertebrae from a basal electric ray, Torpedo californica (Porter et al, 2006)] is much lower than this study's values for the closely related N. bancroftii (25 and 1300MPa, respectively).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Relative proportions were determined by percentage wet mass. Comparative data were obtained from previous publications (Currey, 2002;Macesic and Summers, 2012;Porter et al, 2006;Toppe et al, 2007;Zioupos et al, 2000).…”
Section: Discussionmentioning
confidence: 99%